Missed opportunities for maternal nutrition interventions during antenatal care visits persist in Burkina Faso - Ouédraogo, Césaire T.; Kim, Sunny S.; Zagré, Rock Romaric; Ganaba, Rasmané; Zafimanjaka, Maurice; Sawadogo, Ramatou; Combassere, Roland; Menon, Purnima (American Society for Nutrition, 2020)
High coverage of any antenatal care (ANC) and near-universal coverage of iron-folic acid (IFA) supplementation is reported by nationally representative surveys in Burkina Faso. We examined the coverage of maternal nutrition interventions during ANC to assess gaps and missed opportunities in achieving global and national recommendations.